Yields of Promising Sugarcane Clones under Three Different Planting Arrangements - Prima Diarini Riajaya; Djumali Djumali; Bambang Heliyanto (AGRIVITA, Journal of Agricultural Science, 2022)
A field experiment was conducted at Kediri, East Java, to examine the influence of row spacing on the yield of five promising clones from August 2018-June 2020. The investigation was of a Split-Plot design with three replications. The main plot consisted of three planting arrangements: SR, single row spacing at 110 cm, DR1, double rows spacing 50+135 cm, and DR2, double rows spacing 50+170 cm. Sub-plots consisted of five promising clones and one check variety: MLG 5, MLG 9, MLG 14, MLG 52, MLG 55, and PS 881. The results suggest no overall significant effect of planting arrangement on sugar yield, though clones may vary. There are significant differences in yield between some clones. Wider rows, DR2, show the highest yield in tonnes of cane per hectare (TCH) in PC (153.94 t/ha) with a slight decrease (14%) in RC-1 due to reduced plant population. Sugar yield in tonnes of sugar per hectare (TSH) in various planting arrangements ranges from 12.26-13.99 t/ha in PC and 10.68-11.93 t/ha in RC-1. MLG 9 can be released as a new variety with high cane and sugar yields.Â